Screening of Proteolytic Enzymes of Streptomyces sp. Local Strain and Their Characterization - DERI YURATMOKO; NISA RACHMANIA MUBARIK; ANJA MERYANDINI (Indonesian Society for microbiology, 2007)
Protease of two Streptomyces sp. strain were chosen for characterization because of the large clear zone surrounding the colony in nutrient agar media containing 1% (w/v) skim milk. Extracellular protease from the two isolates SLW 8-1 and 45I-3 were characterized following incubation of the isolate in Nutrient Broth media containing skim milk or chicken feather (1%). The optimum activity of the protease SLW 8-1 was at pH 9 and 80 ºC, whereas that of the keratinase was at pH 6.5 and 70 +C. Protease of strain 45I-3 showed its optimum activity at pH 7.5 and 50 ºC whereas the keratinase was at pH 8.5 and 80 ºC.